Effect of Temperature and CaCO3 Concentration on the CO2 Corrosion Behavior of Carbon Steel in Seawater - Arifin, Zaenal; Cahyono, Yoyok; Purwaningsih, Sri Yani; Suasmoro, Suasmoro; Asrori, Zainul (Jurnal Fisika dan Aplikasinya, 2025)
In oil and gas production, CO2 corrosion and  CaCO3 scale happen simultaneously. Research has been carried out on the corrosion behavior of CO2 on carbon steel samples. Corrosion behavior was analyzed based on changes in temperature (60, 80 and 100 °C) and CaCO3 concentration (0, 700 and 1000 ppm) in seawater environments with CO2 gas at a flow rate of 1 lt/min. The corrosion rate calculation is carried out using the weight loss method. Increasing the concentration of CaCO3 in seawater causes a decrease in the corrosion rate and the greatest corrosion rate occurs at 80 °C. Characterization of corrosion products from deposited powder using XRD and SEM at various temperature changes produces crusts with aragonite, calcite and halite phases. Meanwhile, variations in CaCO3 concentration produce aragonite phases as well as siderite and chukanovite corrosion products with morphologies such as rice grains, rhombohedral, needle-like and plate-likeKeywords: CO2 corrosion, aragonite, siderite and chukanovite